Efektifitas Fungsi Hutan Kota di Surakarta - Gunung Gambiro; Galing Yudhana; Winny Astuti (ARSITEKTURA, 2017)
In limited urban forest in developed cities, the existence of the urban forest is very important to maintain the sustainability of the city. In the era of developed city there are still a lot of urban forest functions considered not important. Thus, the potential of urban forest in the Surakarta currently is expected to be maximized its function in order to be effective. The Problem in this research is how effectively the functions of urban forests in Surakarta. With the aim to determine the efficiency of urban forest based on its functions for the survival existence of an existing green open space in Surakarta currently. Thus the effective functions of the urban forest in Surakarta today become crucial, according to the function of ecological, social, economic and aesthetic. Through observation method and questionnaire as well as the calculation of scoring and linkert scale are expected to provide findings in the research of how effectively the functions of urban forests in Surakarta today. Therefore, in this analysis requires identification of the stages characteristic of urban forest areas, analysis urban forest functions, and analysis the effectiveness of urban forest functions.  From the analysis of the effectiveness urban forest function, it was found that the effectiveness of urban forest functions in Surakarta was not only seen through the effectiveness of quantity but also the quality of the urban forest itself. The effectiveness of urban forest will run well with the commitment of government and society. This research recommendations in the planning area is to give a good management and maintenance and sustainable development that capable producing urban forest function to be more effective in the quality and quantity. Keywords: Green Open Space, Effectiveness, Urban Forest Functions, Quantity and Quality.